Radiography measurements of direct drive imprint in thin Al foils using a bright XUV laser - Warwick, P; Demir, A; Kalantar, D; Key, M; Kim, N; Lewis, C; Lin, J; MacPhee, A; Neely, D; Remington, B; Rose, S; Smith, R; et al. (1996)
A saturated XUV laser operating on the J=0-1, 19.6nm transition of Ne-like Germanium provided an excellent source to provide in-line backlighting for 2D imaged radiography. The imprint of a direct drive laser beam and subsequent Rayleigh-Taylor growth of perturbations in a 2 mu m thick Al foil, irradiated with 0.53 mu m laser light at 2-8x10(12) W/cm(2), was investigated. Measurements are presented for the modulation Slue to random phase plate static speckle, SSD smoothed and ISI smoothed speckle. In addition we present a study of single mode optical imprint generated by the interference pattern of a double rectangular aperture.